Bioavailability study of enantiopure (S)-Equol in CD(SD)IGS rats - Seethakallu Ramachandraiah AnandaKumar; Mukund Handral; Srinivas Seekallu (Scientific Reports)
Abstract The therapeutic potential of (S)-Equol across various health domains, including mental health and oncology has been identified and studied enormously. However, the pharmacokinetic study on the enantiopure (S)-Equol in male and female rats under graded doses remain untouched, and the study concentrates on the same. Male and female CD(SD)IGS rats were grouped into 8 groups and some groups were administered with 20, 60 and 160 mg/kg body weight, orally and other administered with intravenous bolus injection at 10 mg/kg body weight of (S)-Equol. The plasma (S)-Equol concentrations were estimated by LC-MS/MS and the pharmacokinetic parameters determined from the concentration time data by non-compartmental PK analysis. The observed (S)-Equol Cmax was 66.78, 659.38, 2542.02 ng/mL in males and 392.08, 1661.97, 4879.36 in female rats, similarly, the observed (S)-Equol AUCLast was 118.96, 1130.32, 4876.00 h*ng/mL in males and 2164.01, 4883.09, 14067.94 in female rats at 20, 60 and 160 mg/kg dose respectively. The intravenous bolus administration of (S)-Equol showed 8563.25, 8642.91 ng/mL of Cmax and 3742.98, 3551.90 h*ng/mL AUCLast at 10 mg/kg dose in male and female rats respectively. The oral bioavailability of (S)-Equol was found to be 1.59, 5.03, 8.14% in male rats and 30.46, 22.91, 66.01% in female rats at doses of 20, 60 and 160 mg/kg of (S)-Equol administration respectively. These data suggesting that gender related differences in plasma exposure, increased plasma exposure was observed in female rats, plasma exposure at 60 mg/mL in female rats were comparable to the exposures at 160 mg/mL in males rats.